Stability Analysis of Dam with Asphalt Core in Static and Pseudo-Static Conditions - Krisnayanti, Denik Sri; Sir, Tri M. W.; Hangge, Elsy E.; Megonondo, Batara Doa; Klau, Ralno R.; Galla, Andrea Z. (Civil Engineering Journal, 2025)
Manikin Dam was constructed to address the issue of raw water shortage in Kupang Regency and Kupang City. However, there were challenges due to clay materials that did not meet the required specifications. Therefore, this study aimed to use asphalt core design as an alternative by analyzing the stability of the embankment body under both static and pseudo-static conditions. To achieve the aim, the Bishop method was applied using the GeoStudio SLOPE/W application, along with manual calculations. The results showed that the safety factor (SF) at the end of construction without seismic loads met the minimum value of 1.300. Under various water level conditions (FWL, NWL, LWL), SF consistently met the minimum required value of 1.500. Furthermore, the seismic analysis considered both operational base earthquakes (OBE) with a return period of 100 years and maximum design earthquakes (MDE), which had a return period of 5,000 years. Even under OBE and MDE seismic loading conditions, SF exceeded the minimum required value. This implied that the use of an asphalt core could be considered safe in terms of preventing potential landslides under both static and pseudo-static conditions. Based on this outcome, asphalt core became a practical alternative for future dam construction, particularly in areas where clay could be scarce or unstable for technical reasons.